Persepsi Pedagang Kaki Lima Terhadap Kebijakan Pemerintah Di Laman Boenda Kota Tanjungpinang - Sintani, Priti; Nurlianti, Arifa; Halim, Abdul; Candra, Mellyana (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This research examines the perceptions of street vendors in Laman Boenda Tanjungpinang City as stated in the Tanjung Pinang City Regional Regulation No. 7 of 2018 regarding public order. The existence of street vendors in Laman Boenda, Tanjungpinang City is considered to be the cause of traffic jams and destroying the beauty of the city. The aim of this research is to describe how street vendors responded after the government policy regarding public order regarding street vendors. This research uses descriptive research with a qualitative approach. The data collection technique in this research uses literature study techniques which refer to various other sources of information, such as journals, books and other literature reviews. The results of this research show that the response of street vendors to government policy in Laman Boenda, Tanjungpinang City is that there is hidden resistance and covert resistance. The form of hidden resistance that is carried out is that they continue to sell and pay dowries for sales stalls. Meanwhile, the form of open resistance is refusing relocation and holding demonstrations.